Елементарні акти реакції відновлення молекулярного кисню на допованому нітрогеном sp2-вуглецевому кластері: квантовохімічне дослідження - Demyanenko, E. N.; Karpenko, O. S.; Lobanov, V. V.; Kartel, N. T. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2017)
Density functional theory (B3LYP, 6-31 G**) was used to calculate the spatial and electronic structure of the oxygen molecule complexes with the coronene molecule and its nitrogen-containing analog, where two nitrogen atoms are in the para positions of the central hexagon. Within the framework of an assumption that the mentioned molecules mimic a pure carbon and nitrogen-containing graphene-like structures, the equilibrium structures and energis of formation of all the intermediate compounds arising when four electrons and four protons are sequentially added to the adsorption complex of the O2 molecule are determined. It has been shown that the catalytic activity of nitrogen-doped graphene in the oxygen reduction reaction can be explained by a combination of several factors, namely, a decrease in the band gap of the nitrogen-containing cluster as compared to the initial pure carbon cluster as well as the activation of carbon atoms adjacent to the interstitial N atoms. Calculation of the energies of the individual stages of addition of each of four electrons and protons testifies to the spontaneous flow of the oxygen reduction over the nitrogen-containing cluster.